Answer:
Explanation:
1. The expression simplifies to ...
... = 5x² -3xy +7x² +5xy -12x²
... = (5+7-12)x² +(-3+5)xy
... = 2xy
1a. for (x, y) = (-0.25, 4), -2xy = -2
1b. for (x, y) = (-5, 0.1), -2xy = -1
_____
2. To eliminate the terms you don't want, add their opposite.
2a. The terms you don't want are x²-2xy. To get rid of them, add the opposite of this sum: 2xy -x².
2b. The terms you don't want are y²-2xy. Add their opposite: 2xy-y².
_____
Comment on point value
Last time I checked, 5 (or 8) and 50 were very different things.